Untapped potential - choose wisely - Catharine Anna Henderson (Health for All Nations, 2015)
Based on a personal perspective the author derived from a lecture at the American Public Health Association meeting about the power of a choice which can change the course of history, the author presehts a perspective on the choices made regarding ante-natal life and how this effects a loss in human potential and the global health repercussions that can result.